Two-dimensional Layer-by-layer Assembled Graphene Oxide Membranes in Water Treatment. (December 2018) - Fan, Zheng; Wang, Tiecheng; Wang, Ling; Fu, Delong; Song, Shijian; Yin, Qingchuan; Zhang, Guoliang
Abstract: Graphene oxide membranes (GOMs) are ultra-thin, high-throughput and energy-efficient membranes for precise ion and molecular sieving in aqueous solutions. The spacing control of the graphene layer has a great influence on the separation effect of the material, and is of great significance for achieving the balance between the separation degree and the flux. Due to the particularity of the graphene oxide structure, the layer spacing can be precisely manipulated when the multi-layers are self-assembled. Layer-by-layer self-assembly is an important method for preparing graphene oxide membranes. Based on the unique structure and properties of graphene oxide membranes, layer-by-layer self-assembly method and its application is reviewed in this paper.